2016
DOI: 10.1016/j.joms.2016.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Role of Collagen Conduit With Duloxetine and/or Pregabalin in the Management of Partial Peripheral Nerve Injury

Abstract: Using a collagen conduit and duloxetine, pregabalin, and their combination helped alleviate neuropathic pain. The mechanism of action might be associated, at least in part, to cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…However, we demonstrated a significant inhibitory effect of PGB on cytokines secretion in vivo, and in splenocytes but www.nature.com/scientificreports www.nature.com/scientificreports/ not in PMs in vitro. Whilst our data were similar to previous reports in the inhibition of IL-6, IL-1β and TNF-α secretion 19,[38][39][40][41] , careful comparisons should be applied as those reports used different mitogens (carrageenan) 19 , different doses of PGB (at least 30 mg/kg of PGB) 19 , different inflammatory models (hyperglycemic stroke 39 or chronic constriction injury models 40,41 ), different sample for the assessment of cytokines levels (brain tissue 39 or nerve tissue 40,41 ) or even different animal species (rat) 19,[38][39][40][41] . Noteworthy, species, strain-and sex-associated differences in the regulation of some immune responses have been previously reported and similarity in responses is dependent on the outcomes measured [42][43][44][45] .…”
Section: Discussionsupporting
confidence: 93%
“…However, we demonstrated a significant inhibitory effect of PGB on cytokines secretion in vivo, and in splenocytes but www.nature.com/scientificreports www.nature.com/scientificreports/ not in PMs in vitro. Whilst our data were similar to previous reports in the inhibition of IL-6, IL-1β and TNF-α secretion 19,[38][39][40][41] , careful comparisons should be applied as those reports used different mitogens (carrageenan) 19 , different doses of PGB (at least 30 mg/kg of PGB) 19 , different inflammatory models (hyperglycemic stroke 39 or chronic constriction injury models 40,41 ), different sample for the assessment of cytokines levels (brain tissue 39 or nerve tissue 40,41 ) or even different animal species (rat) 19,[38][39][40][41] . Noteworthy, species, strain-and sex-associated differences in the regulation of some immune responses have been previously reported and similarity in responses is dependent on the outcomes measured [42][43][44][45] .…”
Section: Discussionsupporting
confidence: 93%
“…According to the BMI in GSE135917, both OSA and control samples were obese and under chronic inflammation, which may affect the expressions of IL6. Besides, we also found that some of OSA and control individuals were taking medicines, such as duloxetine, insulin and vitamin D, which may either elevate or reduce the expression of IL6 ( 32 34 ). Those characteristics of OSA and control samples used in the current study may cause the conflicted results with previous finding.…”
Section: Discussionmentioning
confidence: 75%
“…On the other hand, another study of pregabalin 10 mg/kg over three weeks did not find an effect on nerve regeneration [60]. A third study found that pregabalin-collagen therapy after injury aided in nerve regeneration by inhibiting IL-10 release, a pro-inflammatory cytokine that negatively impacts the healing processes [61]. Our current study does not provide information on the effects of pregabalin on corneal nerve regeneration and as such, future studies are needed that focus on these connections, such as with the use of confocal microscopy.…”
Section: Discussionmentioning
confidence: 99%